Halal Concept as an International Legal Model for Maintaining Environmental Sustainability: Case Study of Halal Street Food in the US - Nasywa Tsabita Amelia; Rifdah Syifa Rabbani; Ida Susilowati; Novi Rizka Amalia; Afni Regita Cahyani Muis (Journal of Islamic World and Politics, 2024)
Culture is limited to art, customs, language, and food. Globalization makes it easier for this culture to spread across countries, including food. Likewise, the halal concept in the food industry continues to develop rapidly in the United States. This research aims to discover how the halal concept is closely related to the sustainability of life, involving SDG principles, so that the benefits are considered not to cause damage. The research method used this time is library research with a maqashid sharia concept approach. The author also used gastroeconomics to discuss the relationship between culinary delights and economic sustainability in the United States. The findings showed a relationship between the halal concept and international law, maqashid sharia and environmental sustainability, and the implementation of gastroeconomics in maqashid sharia as evidenced by street food in the United States. Halal street food is becoming increasingly important in the American culinary industry due to its good reception by the American public, support on social media, and adaptation to culinary trends.